(untitled) (Medico Legal Update, 2020)
Renal failure (RF) is common disease, it is decrease of kidney function, glomerular filtration rate (GFR) this use to estimate the kidney function reduction usually is less than 60 mL / min, depending on global Burden of Disease, and the disease is ninth cause of death in the world, According to the global Burden of Disease. Our study is investigated in the relationship between IL-17F (rs763780) genes polymorphic variants in renal failure patients in Iraq. This study was accompanied around Iraqi renal failure patients, the period from February to November 2018. This study included 70 patients from Abn-Sina Center for dialysis and kidney disease, and 30 healthy controls. Tetra-primer ARMS-PCR is rapid, effective and developed assay used our study for studying in genotyping polymorphism of IL-17F (rs763780) genes. Result of our report including the correlation between the genotypes of IL-17F (rs763780) and the incidence of renal failure, as the results show a non-marked difference between patients and controls when genotype T/T (OR = 0.75). Also, no significant difference between patients and control when genotype C/C (OR = 0.85), while the genotype T/C (OR = 2.23) show important difference between control and patients more than two times. In conclusion, IL-17F play an essential role as pro-inflammatory cytokine in renal failure patients and development disease.